Cancer chemopreventive effect of bergenin from Peltophorum pterocarpum wood - Jie Zhang (2018)
The aqueous extract of Peltophorum pterocarpum (Fabaceae) wood exhibited potent inhibitory effects against Epstein-Barr virus early antigen (EBV-EA) activation induced with 12-O-tetradecanoylphorbol-13-acetate (TPA) in Raji cells and against melanogenesis in α-melanocyte-stimulating hormone (α-MSH)-stimulated B16 melanoma cells, as well as potent 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical-scavenging activity. Two phenolic acid derivatives, bergenin (1) and gallic acid (2), were isolated from the ethyl acetate (AcOEt)-soluble fraction obtained from the extract. Compound 1 exhibited potent inhibitory effect against EBV-EA activation and against skin tumor promotion in an in vivo two-stage mouse skin carcinogenesis test based on 7,12-dimethylbenz[a]anthracene (DMBA) as initiator, and with TPA as promoter. Both compounds 1 and 2 exhibited melanogenesis-inhibitory activities in α-MSH-stimulated B16 melanoma cells, and, in addition, compound 2 showed strong DPPH radical-scavenging activity. Copyright © 2013 Verlag Helvetica Chimica Acta AG, Zürich.